Analisis Arah dan Kecepatan Angin Permukaan Menggunakan Digaram Wind Rose di Bandara Internasional Sultan Hasanuddin - Prasetiyo, Adi (Buletin GAW Bariri (BGB), 2024)
Sultan Hasanuddin International Airport is situated among hills and lowlands, resulting in highly variable wind patterns. In aviation operations, winds are categorized into three types: headwind, tailwind, and crosswind. The most hazardous for flight operations are tailwinds and crosswinds exceeding 10 knots. To ensure flight safety at Sultan Hasanuddin International Airport, it is essential to understand the patterns of wind direction and speed, which can be analyzed using a wind rose diagram. The data used in this study includes wind direction and speed measurements from 2014 to 2023 obtained from METAR (Meteorological Aerodrome Report) at the Sultan Hasanuddin Class I Meteorological Station. The results indicate that the dominant wind direction from 2014 to 2023 at Sultan Hasanuddin International Airport is from the east (67.5°  –  112.5°), with the highest wind speed recorded during this period being ≥ 21.58 knots. Crosswind or aligned wind conditions with runways 03 – 21 and 13 – 31 still show wind speeds exceeding 10 knots, which poses a potential hazard of crosswinds or tailwinds for aircraft.